Analisis Kebutuhan Tenaga Perpustakaan Di Perpustakaan UIN Raden Fatah Palembang - Nurmalina Nurmalina (THE LIGHT : Journal of Librarianship and Information Science, 2021)
This study aims to determine the number of human resources needed by the library of UIN Raden Fatah Palembang. This research was conducted using a quantitative descriptive method. The data is processed by referring to Law Number 43 of 2007 concerning Libraries and the Regulation of the Head of the National Library of the Republic of Indonesia Number 26 of 2017 concerning Guidelines for the Preparation of the Functional Position Formation of Librarians. The results of this study indicate that the ideal number of librarians in an agency is 24 people. Meanwhile, the number of librarians in the central library of UIN Raden Fatah Palembang is only 4 people. So it is recommended that there is an increase in the number of librarians who have a D II, D III and D IV background or a bachelor (S1) in Library Science.